2021
DOI: 10.1155/2021/9979827
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Pretreatment of Corms by Different Concentrations of Gibberellic Acid and at Different Periods on the Growth, Flowering, and Quality of Saffron in Eastern Morocco

Abstract: The present study was conducted to evaluate the influence of gibberellic acid (25, 50, 100, and 200 ppm) applied on saffron corms previously harvested during different periods (March, June, and before planting) on the growth and the quantitative and qualitative yield of saffron (Crocus sativus L.). The study was carried out in the field during the 2016-2017 and 2017-2018 seasons in the experimental station of the Faculty of Sciences of Oujda (Morocco). The measured parameters correspond, on the one hand, to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Use of CCC @ 600 and 800ppm produced the lowest number of suckers, which was much less than control treatment. This is in agreement with the findings of Mzabri et al [28]. The higher number of sucker production by using GA 3 might be due to increase the number and size of leaves as a result of higher translocation of the photosynthates and eventually that would have been used for the production of propagules (suckers).…”
Section: Effect Of Growth Regulators On the Production Of Suckers In ...supporting
confidence: 92%
See 1 more Smart Citation
“…Use of CCC @ 600 and 800ppm produced the lowest number of suckers, which was much less than control treatment. This is in agreement with the findings of Mzabri et al [28]. The higher number of sucker production by using GA 3 might be due to increase the number and size of leaves as a result of higher translocation of the photosynthates and eventually that would have been used for the production of propagules (suckers).…”
Section: Effect Of Growth Regulators On the Production Of Suckers In ...supporting
confidence: 92%
“…The C. indicum flower has a strong aroma and many of the previous studies focused on the essential oil of this plant [13]- [15]. Khan et al [16] observed that the plant height (54.0 to 66.0 cm); number of leaves per plant (208-240); leaf size (4.5 to 8.5 cm); plant spread (19.0 to 32.0 cm); number of branches (4 to 12); number of flowers (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); stalk length (8.8 to 13.3 cm) and days of first flowering (55 to 70 days) varied; respectively in T 7 (100% rice husk) to T 3 (100% cocodust). The different color of leaves and flowers in chrysanthemum flower crop and also the maximum flower period was observed early December-February in germplasms.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of GA on ower characteristics could be because of its effect on photosynthesis activity which led to an increment in metabolic processes in plants(Ghatas 2016). In agreement with our study,Mzabri et al (2021) expressed that saffron corms which were soaked by GA reached ower time sooner. GA regulates the leaves sugar content by stimulating the sucrose phosphate synthase enzyme activity in plants(Kozłowska et al 2007).…”
supporting
confidence: 92%
“…The experimental research took place within the open field located at the research station of the Faculty of Sciences in Oujda, Morocco, over a three-month duration. This experimental station is situated at an altitude of 661 meters, with coordinates of 34° 39' 06.71'' North and 01° 53' 58.80'' (Mzabri et al, 2021). The local climate is characterized as arid with mild winters.…”
Section: Experimental Sitementioning
confidence: 99%